Supervisory and statistical granular data modelling at the Croatian National Bank - Ines Bašić (European Central Bank (ECB), 2017)
As the European Reporting Framework (ERF): Key facts and information1 report has recognised, some countries have already implemented integrated "statistical" and supervisory reporting requirements at a granular level. Croatia is one of these countries. Moreover, Croatia has been able to produce a local "AnaCredit" system on a loan-by-loan basis for legal entities and non-residents (see the ECB MFI list2 or Annex 4 of the Banks' Integrated Reporting Dictionary of the Croatian National Bank3), and at an aggregate level for households, other non-residents and small businesses, using the same underlying data as for statistical and prudential reporting. A Croatian granular data system at a counterparty level for legal entities/non-residents on the list and at an aggregate level for households, other non-residents and small businesses was developed in 2007/2008 following a series of workshops held among colleagues from Supervision, Statistics and IT at the Croatian National Bank (CNB) and credit institutions. One of the most important deliverables of the project was the CNB Banks' Integrated Reporting Dictionary, a document in which all attributes collected by the system are listed, organised into categories, described and explained, and where examples and the methodologies used are provided. In Croatia, the CNB Banks' Integrated Reporting Dictionary is mandatory for all credit institutions, and it has been enforced on the financial market following a decision of the Croatian National Bank Governor. This article discusses granular data modelling for the purpose of statistical, supervisory and European Central Bank reporting and analysis.
Keywords: E58; C81; G28; 330; granular data; modelling; metadata; data warehouse; Croatian National Bank